Effects of Human–Dog Interactions on Salivary Oxytocin Concentrations and Heart Rate Variability: A Four-Condition Cross-Over Trial. (2nd January 2020) - Powell, Lauren; Edwards, Kate M.; Michael, Scott; McGreevy, Paul; Bauman, Adrian; Guastella, Adam J.; Drayton, Bradley; Stamatakis, Emmanuel
ABSTRACT: Dog ownership is often advocated for its potential benefits to human health, with changes to oxytocin and autonomic nervous system (ANS) activity proposed as possible underlying mechanisms. The aims of the current study were to a) examine the effect of two common types of human–dog interactions (dog-walking and affiliative interactions) on salivary oxytocin concentrations and heart rate variability (HRV, an indicator of ANS activity), and b) investigate any putative moderating role for the strength of human–dog attachment on such responses. Twenty-nine dog owners completed a four-condition random-order cross-over trial: dog-walking (DW); walking without the dog (W); affiliative human–dog interaction (H-DI); and resting without the dog (C). Each condition was performed for approximately 15 minutes. Saliva and HRV samples were collected before and after each condition. Linear mixed models were used to analyze data, with the participant considered a random effect; condition, order of conditions, and condition duration as fixed effects. Oxytocin concentrations were not significantly different following any of the four conditions. HRV was significantly reduced following DW (mean change HF HRV = –0.37, 95% CI = –0.70, –0.04) and W (mean change HF HRV = –0.49, 95% CI = –0.81, –0.17). Considering moderation by the strength of the human–dog bond, pairwise comparisons revealed that, compared with W, DW elicited an increase in oxytocin concentrations (mean change 9.32 pg/mL, 95% CI = 6.52, 12.12) and HRV (mean change SDRR = 0.41, 95% CI = 0.19, 0.63) in owners with lower levels of attachment. These owners also displayed increased oxytocin concentrations following H-DI (mean change 3.90 pg/mL, 95% CI = 1.48, 6.32), compared with C. Overall, we did not find a consistent pattern for positive oxytocin or HRV responses to human–dog interactions. The strength of owner–dog attachment was found to have a moderating effect, suggesting that human–dog interactions may elicit greater physiological responses in low-attachment individuals.